The Formation of Students’ Islamic Leadership Character through OSIS Activities: A Qualitative Study at Al-Ishlah Islamic Junior High School, Bukittinggi - Amelia, Amelia; Charles, Charles (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
Research on student organizations has recognized their potential to support character and leadership development; however, less is known about how Islamic leadership character is formed through organizational practices in Islamic junior high schools. This study examines the formation of students’ Islamic leadership character through Intra-School Student Organization (Organisasi Siswa Intra Sekolah, OSIS) activities at Al-Ishlah Islamic Junior High School, Bukittinggi. It focuses on organizational practices, supporting and constraining conditions, and school members’ perceptions of the effects of OSIS participation. Using a descriptive qualitative design, the study involved nine informants: one principal, two OSIS advisors, three core OSIS administrators, and three active OSIS members. Data were collected from January to March 2026 through approximately eight weeks of moderate-participation observation, semi-structured interviews, and documentary review. The data were analyzed through condensation, display, and conclusion drawing or verification, with source and method triangulation supporting trustworthiness. The findings indicate that Islamic leadership character was formed through leadership training, role modeling, religious habituation, deliberative meetings, the allocation of organizational responsibilities, and social activities. The process was supported by the school’s religious environment, advisor guidance, parental support, peer cooperation, and students’ willingness to participate. Limited time, dense academic and organizational schedules, and the need for continued supervision constrained implementation. Participants perceived OSIS participation as associated with greater responsibility, discipline, confidence, communication skills, and willingness to cooperate. OSIS thus functioned as a supervised setting in which students practiced Islamic leadership values in everyday organizational life.